Omega-3 polyunsaturated fatty acids antagonize macrophage inflammation via activation of AMPK/SIRT1 pathway. - Bingzhong Xue (Public Library of Science (PLoS), 2012)
Macrophages play a key role in obesity-induced inflammation. Omega-3 polyunsaturated fatty acids (ω-3 PUFAs) eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) exert anti-inflammatory functions in both humans and animal models, but the exact cellular signals mediating the beneficial effects are not completely understood. We previously found that two nutrient sensors AMP-activated protein kinase (AMPK) and SIRT1 interact to regulate macrophage inflammation. Here we aim to determine whether ω-3 PUFAs antagonize macrophage inflammation via activation of AMPK/SIRT1 pathway. Treatment of ω-3 PUFAs suppresses lipopolysaccharide (LPS)-induced cytokine expression in macrophages. Luciferase reporter assays, electrophoretic mobility shift assays (EMSA) and Chromatin immunoprecipitation (ChIP) assays show that treatment of macrophages with ω-3 PUFAs significantly inhibits LPS-induced NF-κB signaling. Interestingly, DHA also increases expression, phosphorylation and activity of the major isoform α1AMPK, which further leads to SIRT1 over-expression. More importantly, DHA mimics the effect of SIRT1 on deacetylation of the NF-κB subunit p65, and the ability of DHA to deacetylate p65 and inhibit its signaling and downstream cytokine expression require SIRT1. In conclusion, ω-3 PUFAs negatively regulate macrophage inflammation by deacetylating NF-κB, which acts through activation of AMPK/SIRT1 pathway. Our study defines AMPK/SIRT1 as a novel cellular mediator for the anti-inflammatory effects of ω-3 PUFAs.